2014
DOI: 10.3846/13923730.2013.871330
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Building Design

Abstract: Abstract. Sustainable building design has become a wide and multidisciplinary research endeavor including mechanical, electrical, electronic, communication, acoustic, architectural, and structural engineering. It involves the participation of owners, contractors, suppliers and building users. There has been a lot of talk about sustainable buildings in the past few years. Most of the published research is concerned with saving energy and water and making the buildings more environmentally friendly by, say, redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 38 publications
2
70
0
1
Order By: Relevance
“…The negative environmental impacts of rapidly growing world energy consumption as well as vision of energy efficient sustainable buildings was discussed in the last decade [1][2][3][4] pointing that a successful creation of sustainable infrastructure systems, energy efficient and environmentally-conscious designs requires a holistic, integrated, and multidisciplinary approach. Unfortunately, because of the large number and diversity of participants, construction work is characterised by a fragmented decision-making process, fear of venture, and conservatism, which result in innovation avoidance and missed opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…The negative environmental impacts of rapidly growing world energy consumption as well as vision of energy efficient sustainable buildings was discussed in the last decade [1][2][3][4] pointing that a successful creation of sustainable infrastructure systems, energy efficient and environmentally-conscious designs requires a holistic, integrated, and multidisciplinary approach. Unfortunately, because of the large number and diversity of participants, construction work is characterised by a fragmented decision-making process, fear of venture, and conservatism, which result in innovation avoidance and missed opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid growth of this industry in the coming years, and the need for materials as well as waste generation, the use of sustainable materials and technologies in this industry will be a major contributor to sustainable development. Regarding these issues, the evaluation of construction projects based on the dimensions of sustainable development is very essential [6]. In an article named "designing sustainable construction", it is stated that extensive and multi-fields efforts in mechanics, electronic and electrical devices, communication, acoustics, architecture, and structural engineering are made all over the world for designing sustainable constructions.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that saving energy and water and making constructions compatible with the environment significantly prevents carbon dioxide emission in the atmosphere. This study presents strategies for designing sustainable constructions, using the integration of smart structure technology and a combination of semi-active vibration control that lead into lighter and more efficient constructions [6]. In one study, authors identified key criteria of construction, and using fuzzy analytic hierarchy process assessed smart constructions.…”
Section: Introductionmentioning
confidence: 99%
“…The vision of sustainable building was discussed in the last decade (Adeli 2002;Ali, Armstrong 2008;Wang, Adeli 2013;Kaczorek, Koczyk, 2013;Parasonis et al 2012;Džiugaitė-Tumėnienė et al 2012;Brauers et al 2012) pointing that a successful creation of sustainable infrastructure systems and environmentally-conscious designs requires a holistic, integrated, and multidisciplinary approach. Unfortunately, because of the large number and diversity of participants, construction work is characterised by a fragmented decision-making process, fear of venture, and conservatism, which result in innovation avoidance and missed opportunities (Altwies, Nemet 2013).…”
Section: Introductionmentioning
confidence: 99%